PERCUTANEOUS ELECTROLYSIS IN THE TREATMENT OF TENDINOPATHY – A SYSTEMATIC REVIEW - Magdalena Rosiewicz; Karolina Bieńkowska; Anita Janda; Sylwia Bartolik; Marcin Durowicz; Iwona Górnicka; Aleksandra Pastuszek; Jan Drzymała; Urszula Kierepka (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Percutaneous electrolysis (PNE/EPI) is a minimally invasive technique used in the management of tendinopathies. The mechanism of action of this compound is based on the induction of a localised electrochemical reaction, which in turn triggers a controlled inflammatory response. This inflammatory response serves to promote the resorption of degenerated tissue and to stimulate collagen regeneration. In recent years, this method has gained increasing popularity as an alternative or adjunct to conventional conservative therapies, such as eccentric exercise, extracorporeal shockwave therapy (ESWT), or platelet-rich plasma (PRP) injections. A mounting body of clinical evidence, encompassing randomised controlled trials, has emerged to support the efficacy of this approach in alleviating pain and enhancing function in patients afflicted with chronic tendinopathy.. Objective: This systematic review aims to evaluate the existing evidence regarding the effectiveness and clinical relevance of percutaneous electrolysis in the treatment of tendinopathy. Materials and Methods: The article is based on scientific literature sourced from PubMed and Google Scholar. Results: PNE demonstrates beneficial effects on pathologically altered tendons. The majority of studies report pain reduction and functional improvement in patients. The combination of PNE with other therapeutic modalities shows a synergistic effect. Nevertheless, further comparative analyses and meta-analyses are required to definitively establish the superiority of PNE over other treatment approaches. Conclusions: PNE may serve as a core component in the treatment of tendinopathy. However, standardization of treatment parameters—such as current intensity and therapeutic protocols—is necessary to ensure consistency and reproducibility of outcomes.